Authentication System of Online Student Profiles with Blockchain Algorithm - Özvataf, Sermet Eser (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Nowadays, use of internet by more people made the demand towards online education increase. Together with the integration of education and technology, these trainings have become available as a new channel on digital platforms. Therefore, educational institutions, especially universities and private enterprises have started to offer courses they provide in physical settings in online platforms as well. Just as in the courses given in the physical settings, when the determined learning outcomes are achieved, this success is documented through certificates or diplomas. Although, the concepts such as educational content and student information in educational institutions' own information systems are not digitally portable and shareable, it still needs a lot of work flow based on manpower and physical documentation which carries qualities that lack behind the online technologies, unreliable and also not without integration problems. In the scope of this work, it is aimed to provide a system where the data of the educational background of individuals can be stored and verified using blockchain algorithms. Blockchain is a distributed recording system that can be shared by many parties, facilitating the recording of new processes while making it easier to monitor over the network of an unbreakable data set. Along with the fact that data security, verifiability and durability can be ensured in electronic form by using only blockchain, it also enables learning records to be stored and shared without a central authority. Another advantage of verifiability is to prevent imitation of the identity and documents of educational institutions and to protect the dignity of both academic and non-academic institutions. In addition to the basic facilities provided by the Blockchain system, the new possibilities and uses that come up with the combination of learning needs and technology are evaluated. It is an example of the fact that students are not limited to the educational opportunities of an educational iv institution but can also provide the educational resources of the fields they want to specialize from different educational institutions. The educational plans that can be obtained through digitalized data are considered as new advantages that can be offered to institutions and education designers. This study goes through an exemplary application design to address the assessments identified. Keywords: Blockchain, Certification, Diploma, Transcript, E-Learning, Educational Technologies, Information Systems, Verification.

ÖZ:Günümüzde, internetin daha çok insan tarafından kullanılır hale gelmesi, online eğitimlere olan talebi arttırmıştır. Eğitim ve teknolojinin entegrasyonu ile birlikte, talep edilen bu eğitimler yeni bir kanal olarak dijital platformlar üzerinden de arz edilebilir hale gelmiştir. Bu nedenle; üniversiteler ve özel girişimler başta olmak üzere, eğitim kurumları fiziksel ortamlarda verdikleri dersleri online olarak da sunmaya başlamışlardır. Fiziksel ortamlarda verilen derslerde olduğu gibi, belirlenen eğitim hedeflerine ulaşıldığında bu başarı durumu sertifikalar veya diplomalar aracılığıyla belgelendirilmektedir. Ancak eğitim kurumlarının kendi bilgi sistemlerinde yer alan eğitim içeriği ve öğrenci bilgisi gibi kavramlar dijital anlamda taşınabilir ve paylaşılabilir niteliklerde olmadığı için online teknolojilerin gerisinde kalmış, güvenilebilirlik ve entegrasyon sorunları nedeniyle halen fiziksel evrak ve insan gücüne bağlı birçok iş akışına gereksinim duymaktadır. Bu çalışma kapsamında; blockchain algoritmaları kullanılarak bireylerin eğitim geçmişlerine ait verilerin saklanabildiği ve doğrulanabildiği bir sistem sunmak amaçlanmaktadır. Blockchain, bütünlüğü bozulamaz bir veri dizisi üzerinde yeni işlemlerin kaydedilmesini ve bunların ağ üzerinden izlenme sürecini kolaylaştıran, birçok parti tarafından paylaşılabilir, dağıtık bir kayıt sistemidir. Yalnızca blockchainden yararlanılarak, elektronik ortamda veri güvenliği, doğrulanabilirliği ve kalıcılığı sağlanılabilmekle birlikte; bir merkezi otorite olmaksızın öğrenim kayıtları saklanılabilir ve paylaşılabilir. Doğrulanabilirliğin getirdiği bir diğer avantaj eğitim kurumlarına ait kimlik ve evrakların taklit edilmesi önlemek ve hem akademi hem de akademi dışındaki dünya için kurumların itibarlarının korunmasını sağlamaktır. Blockchain sisteminin sağladığı temel imkanlara ek olarak, öğrenim ihtiyaçları ve teknolojinin birleşimiyle açığa çıkan yeni olanak ve kullanımlar da değerlendirilmektedir. vi Öğrencilerin bir eğitim kurumunun eğitimsel olanakları ile sınırlı kalmayıp uzmanlaşmak istedikleri alanlara ait eğitim kaynağını farklı eğitim kurumlarından temin etmesi buna bir örnektir. Yine dijitalleşmiş veri sayesinde elde edilebilecek eğitim planlamaları bir eğitim teknolojisi olarak kurum ve eğitim tasarımcılarına sunulabilecek yeni faydalar olarak düşünülmektedir. Bu çalışma saptanan değerlendirmeleri ele almak için örnek bir uygulama tasarımı üzerinden gitmektedir. Anahtar Kelimeler: Blockchain, Sertifikasyon, Diploma, Transkript, E-Öğrenme, Eğitim Teknolojileri, Bilgi Sistemleri, Doğrulama.
Master of Science in Information and Communication Technologies in Education. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technology, 2019. Supervisor: Assoc. Prof. Dr. Ersun İşçioğlu
Keywords: Information and Communication Technologies in Education-Higher Education; E-Learning-Online Education; Education - Computer network resources; Educational Technology-E-Learning; Teaching - Computer network resources; Blockchain; Certification; Diploma; Transcript; E-Learning; Educational Technologies; Information Systems; Verification